Evaluation of fungal growth interactions for the formation of viable fungal mixed culture - Abass Olanrewaju, Alade; Jameel, Ahmad Tariq; Muyibi, Suleyman Aremu; Abd Karim, Mohd Ismail; Alam, Md. Zahangir (IBS 2012 Secretariat, 6F, Sunghwa Bldg. 1356-51 Manchon1-dong, Suseong-gu, Daegu 706-803, Korea, 2012)
Fungal interactions involving Aspergillus niger, Trichoderma virige, Penicillium, Phanerochaete chyysosporium, and newly isolated fungi (TRQ1, TRQ2 and TRQ3) from Sludge Palm Oil (SPO) was successfully studied. Number of possible pairing was achieved from the permutation and combination formula. Thus 21 combinations obtained were grown on potato dextrose agar (PDA) media in disposable Petri-dish, inoculated (pin-point) with two fungi at a time, 4cm apart. The growth diameter of each microorganism was recorded on day 7, in order to determine the average growth ratio towards each other. Furthermore, the plates were examined for possible secretions and inhibitions between any combined fungi in the dish. The nature of the combinations were observed as compatible (mutual and partial) and incompatible (secretion and inhibition). 19%, 24%, 19%, 29% and 10% of the mixed cultures showed mutual mingling, partial mutual mingling, replacement/ invasion interaction, ‘deadlock at distance’ and ‘Deadlock at contact’, respectively. The percentage spread of Aspergillus niger, Trichoderma virige, Penicillium, and Phanerochaete chyysosporium, were generally higher than those of the new isolates TRQ1, TRQ2 and TRQ3) for all the mixed cultures involving the isolates. Furthermore, TRQ2 and TRQ3 spread faster than TRQ1, while TRQ3 spread faster than TRQ2. Similarly, Trichoderma virige spread faster in a mixture culture with Penicillium, Phanerochaete chyysosporium and Aspergillus niger, while Phanerochaete chyysosporium spreads faster than Aspergillus niger, yet Aspergillus niger spreads faster than Penicillium in the mixed culture. This study thus provides a platform for the selection of viable mixed culture of microorganisms for biodegradation and bioconversion in biotechnology.